KONSEP PEMBELAJARAN PENDIDIKAN AGAMA ISLAM DI ERA SOCIETY 5.0 - Syamsul Bahri (Edupedia : Jurnal Studi Pendidikan dan Pedagogi Islam, 2022)
Azyumardi Azra highlighted the importance of modernizing Islamic religious education so that the Islamic paradigm can be applied not only to Muslims but also to the whole world. The new national education paradigm also underscores the fact that Islamic educational institutions are basically community-based, namely community-based education. Revitalization of the learning system, educational units, elements of students, educators and education staff all play a role in the effectiveness of PAI learning in line with the idea of ​​Islamic religious education. If all the important components in PAI learning education are able to keep up with the times, especially towards the use of digital, then the implementation of PAI learning education will become more digital, think creatively, be more imaginative, and dynamic. In the era of society 5.0, when almost all educational activities rely on advances in digital technology, the PAI learning process is needed to compete in the use of technology and information in learning activities. An PAI educator as an innovator in the field of Islamic religious education must be able to take advantage of digital learning applications through e-learning, namely Zoom, Google Meet, Discord, gSuite for edu, edmodo, kahoot, and learning houses, intended to make PAI learning more compatible and able to generate generations Muslim superior and capable.